Carbon black with high thermal conductivity and preparation method thereof, and tire bladder

By using carbon black with high thermal conductivity as a filler for tire capsules, the problem of insufficient thermal conductivity of existing tire capsules is solved, and the effect of significantly improving thermal conductivity and extending service life is achieved, while reducing production costs.

CN117720829BActive Publication Date: 2025-04-25JIAOZUO CITY HEXING CHEMICAL INDUSTRY CO LTD

Patent Information

Application Number
CN202311792327.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-25
Publication Date
2025-04-25
Estimated Expiration
2043-12-25

AI Technical Summary

Technical Problem

The thermal conductivity of existing tire capsules is insufficient, resulting in long vulcanization time and low service life, making it difficult to meet market demand.

Method used

Carbon black with a thermal conductivity of 0.1462 to 0.2097W/m·K is used as the filler. The average particle size of the primary particles of the carbon black is 25 to 45 nm, including carbon spheres and epitaxial carbon layers. The thermal conductivity of carbon black is improved through specific preparation methods and process parameters.

Benefits of technology

It significantly improves the thermal conductivity of tire capsules, extends service life, and reduces production costs, meeting the requirements for thermal conductivity and cost of high-performance tire manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117720829B_ABST
    Figure CN117720829B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of carbon black materials, and in particular to a carbon black with high thermal conductivity, a preparation method thereof, and a tire bladder. The carbon black with high thermal conductivity has a thermal conductivity of 0.1462 to 0.2097 W / m·K; the average particle size of the primary particles of the carbon black is 25 to 45 nm; the primary particles of the carbon black include carbon spheres and an epitaxial carbon layer located on the surface of the carbon spheres. The carbon black of the present invention can improve the thermal conductivity of the carbon black by up to 79% compared with the commonly used commercial carbon black, significantly improves the thermal conductivity of the carbon black, helps to improve the thermal conductivity of the tire bladder while maintaining its service life, and saves costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon black materials, and in particular to carbon black with high thermal conductivity, a preparation method thereof, and a tire bladder. Background Art

[0002] The tire bladder is mainly a tool for tire vulcanization. It is an important mold in the tire preparation process and the inner mold of the tire mold. During the tire vulcanization process, the tire bladder is mainly filled with compressed air, nitrogen or superheated water to stretch it and support the tire rubber blank to form an internal pressure vulcanized tire. The outside of the green tire is in direct contact with the steel mold. Since the thermal conductivity of the steel mold is better than that of the vulcanization bladder, improving the thermal conductivity of the vulcanization bladder can shorten the vulcanization time of the green tire, thereby saving energy, improving production efficiency and reducing production costs.

[0003] In the common tire bladders at present, conventional carbon black is used as reinforcing filler, and the thermal conductivity of the tire bladder obtained is low, resulting in a long curing time and a short service life of the curing bladder, which is difficult to meet market demand. In the prior art, the thermal conductivity and thermal efficiency of the tire bladder are improved by blending materials with high thermal conductivity (such as graphene, carbon nanotubes, fiber fillers, etc.), but this will introduce problems of dispersibility and cost. Therefore, how to balance improving the thermal conductivity of the curing bladder and maintaining a good service life and low cost is a technical problem in this field.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide carbon black with high thermal conductivity and a preparation method thereof, and a tire bladder. The carbon black of the present invention has excellent thermal conductivity, can significantly improve the thermal conductivity of the tire bladder while maintaining its service life, and saves costs.

[0006] In order to achieve the above-mentioned object of the present invention, the present invention provides, on one hand, carbon black with high thermal conductivity, wherein the thermal conductivity of the carbon black is 0.1462 to 0.2097 W / m·K;

[0007] The average particle size of the primary particles of the carbon black is 25-45 nm; the primary particles of the carbon black include carbon spheres and epitaxial carbon layers located on the surfaces of the carbon spheres.

[0008] In a specific embodiment of the present invention, the carbon black satisfies the following characteristics:

[0009] (a) BET specific surface area is 70 to 160 m 2 / g;

[0010] (b) DBP oil absorption value is 240~350cm 3 / 100g;

[0011] (c) In the 2D Raman spectrum with an excitation wavelength of 532 nm, the -1 The full width at half maximum of the 2D Raman scattering peak in the range of Δ2D is 118-128 cm -1 The ratio of the peak intensity of the 2D Raman scattering peak to the peak intensity of the G Raman scattering peak is 0.32-0.61, and the plane size of the Raman crystallite is

[0012] In a specific embodiment of the present invention, the crystallinity of the carbon black is 45% to 50%, such as 47% to 50%.

[0013] In a specific embodiment of the present invention, the thermal conductivity of the carbon black is 0.1541 to 0.2097 W / m·K.

[0014] In a specific embodiment of the present invention, the carbon black is acetylene black.

[0015] In a specific embodiment of the present invention, the epitaxial carbon layer is in-situ grown on the surface of the carbon sphere.

[0016] Another aspect of the present invention provides a method for preparing any one of the above-mentioned carbon blacks, comprising the following steps:

[0017] Acetylene and methane undergo thermal cracking reaction in an environment containing carbon dioxide and isolated from air to form carbon black.

[0018] In a specific embodiment of the present invention, the flow ratio of the acetylene, the methane and the carbon dioxide is 20:5:(2-7).

[0019] In a specific embodiment of the present invention, the gas flow directions of the acetylene and the methane are opposite, and the gas flow direction of the carbon dioxide is arranged at an angle to the gas flow directions of the acetylene and the methane. Further, the angle is 45° to 60°.

[0020] Another aspect of the present invention provides a tire bladder, comprising a rubber matrix and a filler; the filler comprises any one of the carbon blacks described above.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The carbon black of the present invention can improve the thermal conductivity by up to 79% compared with the commonly used carbon black on the market, which significantly improves the thermal conductivity of the carbon black, helps to improve the thermal conductivity of the tire bladder while maintaining its service life, and saves costs;

[0023] (2) The method for preparing carbon black of the present invention has a simple process and is easy to produce on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 A schematic diagram of the structure of an apparatus for preparing carbon black with high thermal conductivity provided in an embodiment of the present invention;

[0026] Figure 2 A schematic top view of a nozzle and a furnace head provided in an embodiment of the present invention;

[0027] Figure 3 This is a transmission electron microscope image of the carbon black prepared in Example 1 of the present invention;

[0028] Figure 4 for Figure 3 A partial magnified view of the transmission electron microscope image;

[0029] Figure 5 for Figure 3 Another partial enlarged view of the transmission electron microscope image;

[0030] Figure 6 The Raman spectrum of the carbon black prepared in Example 1 of the present invention;

[0031] Figure 7 The Raman spectrum of the carbon black prepared in Example 2 of the present invention;

[0032] Figure 8 This is the Raman spectrum of the carbon black prepared in Example 3 of the present invention.

[0033] Fig. 9 is the Raman spectrum of the carbon black of Comparative Example 1 of the present invention;

[0034] Fig.10 This is the Raman spectrum of the carbon black prepared in Comparative Example 2 of the present invention.

[0035] Reference numerals:

[0036] 10-cracking furnace body; 11-reaction chamber; 12-furnace head;

[0037] 13-nozzle; 14-gas inlet pipe; 15-discharge port;

[0038] 131 - first nozzle; 132 - second nozzle. DETAILED DESCRIPTION

[0039] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0040] Carbon black can be used as a common reinforcing filler in the preparation of tire bladders. However, with the rapid popularization of radial tires, high-performance tire manufacturing has also put forward higher requirements on the standards of tire bladders. In order to balance improving the thermal conductivity of the vulcanization bladder and maintaining a good service life and low cost, it is necessary to further improve the thermal conductivity of carbon black and maintain the other properties.

[0041] Based on this, the present invention provides, on one hand, carbon black with high thermal conductivity, wherein the thermal conductivity of the carbon black is 0.1462 to 0.2097 W / m·K;

[0042] The average particle size of the primary particles of carbon black is 25 to 45 nm; the primary particles of carbon black include carbon spheres and epitaxial carbon layers located on the surfaces of the carbon spheres.

[0043] The thermal conductivity is tested using a thermal constant analyzer (Hot Disk). For example, in different embodiments, the thermal conductivity of carbon black can be 0.1462 W / m·K, 0.15 W / m·K, 0.16 W / m·K, 0.17 W / m·K, 0.18 W / m·K, 0.19 W / m·K, 0.20 W / m·K, 0.2097 W / m·K, or a range consisting of any two of them.

[0044] The inventors have found through research that when the BET specific surface area, DBP absorption value and 2D Raman spectrum of carbon black meet certain requirements at the same time, the thermal conductivity of the corresponding carbon black can be significantly improved, thereby meeting the high requirements of high-performance tire manufacturing for tire capsules.

[0045] Among them, theoretically speaking, the larger the BET, the smaller the primary particles of the material, the more primary particles under the same mass, the more can be piled up to build a richer thermal conductivity network, and the better thermal conductivity performance. However, the smaller the primary particles, the greater the intermolecular force of conventional carbon black will be, which will introduce dispersion problems during downstream blending applications, leading to local heating and other problems in downstream products. Based on this, the inventors further discovered that when an epitaxial carbon layer structure is introduced on the surface of carbon black and the surface of carbon black is etched to a certain extent, on the one hand, the dispersion is significantly improved, and on the other hand, the surface contact between carbon black particles and between carbon black and other materials can be increased, the thermal conductivity network is expanded, and the thermal conductivity is further improved.

[0046] The DBP oil absorption value and 2D Raman spectrum are parameters of carbon black in the microscopic field. Among them, the DBP oil absorption value can characterize the void volume inside the carbon black aggregate. Introducing new structures on the carbon black surface and etching the carbon black surface both increase the void volume inside the carbon black aggregate to a certain extent, that is, the DBP oil absorption value becomes larger, which also shows that the chain branch structure of carbon black is more developed, making the thermal conductive network more developed and the thermal conductivity better. The specific number of layers and stacking method of the epitaxial carbon layer structure introduced in the carbon black can be reflected by the 2D Raman spectrum.

[0047] Therefore, it is necessary to precisely and quantitatively control the range of each parameter so that carbon black has a better thermal conductive network and high thermal conductivity.

[0048] In a specific embodiment of the present invention, carbon black satisfies the following characteristics:

[0049] (a) BET specific surface area is 70 to 160 m 2 / g;

[0050] (b) DBP oil absorption value is 240~350cm 3 / 100g;

[0051] (c) In the 2D Raman spectrum with an excitation wavelength of 532 nm, the -1 The full width at half maximum of the 2D Raman scattering peak in the range of Δ2D is 118-128 cm -1 The ratio of the peak intensity of the 2D Raman scattering peak to the peak intensity of the G Raman scattering peak is 0.32-0.61, and the plane size of the Raman crystallite is

[0052] The BET specific surface area is tested according to the method of GB / T19587-2004. For example, in different embodiments, the BET specific surface area of ​​carbon black can be 70 m 2 / g, 80m 2 / g, 90m 2 / g、100m 2 / g, 110m2 / g, 120m 2 / g, 130m 2 / g, 140m 2 / g, 150m 2 / g, 160m 2 / g or a range consisting of any two of them.

[0053] The DBP oil absorption value is determined using the standard method of "GB / T 3780.2-2017 Carbon Black Part 2: Determination of Oil Absorption Value". For example, in different embodiments, the DBP oil absorption value of carbon black can be 240 cm 3 / 100g、250cm 3 / 100g、256cm 3 / 100g、300cm 3 / 100g、350cm 3 / 100g or any range consisting of two thereof.

[0054] The specific 2D Raman spectroscopy test method and test parameters are as follows:

[0055] Using a laser Raman spectrometer, several particles of the carbon black sample to be tested are placed on a glass slide, scraped several times with a spatula to make it flat, and tested under the following test conditions: YAG laser (excitation wavelength): 532nm, number of lines: 600gr / mm, filter: D0.6, objective lens magnification: 100 times, exposure time: 150 seconds, cumulative number of times: 2 times. The Raman crystallite plane size (La) is measured by Raman spectroscopy, and regression analysis obtains the following empirical relationship: La = 43.5 × (area of ​​G band / area of ​​D band), where La is calculated in angstroms. The crystal domain of carbon black can be characterized by La, which can give an indication of the degree of graphitization. The higher the La value, the higher the degree of graphitization.

[0056] For example, in different embodiments, in the 2D Raman spectrum of carbon black with an excitation wavelength of 532 nm, the peak position range of the 2D Raman scattering peak can be selected from but not limited to 2670 cm -1 、2675cm -1 、2680cm -1 、2685cm -1 、2690cm -1 or any two thereof; the full width at half maximum Δ2D corresponding to the 2D Raman scattering peak can be selected from but not limited to 118 cm -1 、120cm -1 、122cm -1 、124cm -1 、125cm -1 、126cm -1 、128cm-1 Or the range of any two of them; The peak intensity of the 2D Raman scattering peak (I 2D ) and the peak intensity of the G Raman scattering peak (I G ) ratio I 2D / I G The Raman crystallite plane size of carbon black can be selected from but not limited to 0.32, 0.43, 0.45, 0.50, 0.51, 0.53, 0.55, 0.57, 0.59, 0.61 or any two thereof. Or a range consisting of any two of them.

[0057] In a specific embodiment of the present invention, the crystallinity of the carbon black is 45% to 50%, such as 47% to 50%. The crystallinity can be used to characterize the graphitization degree of the carbon black, which is measured in Raman spectroscopy as the ratio of the intensity of the G band to the sum of the intensities of the G band and the D band (I G / I G+D The carbon black of the present invention has a high degree of graphitization. When the carbon black is used as a filler for rubber, a heat-conducting network can be formed in the rubber, thereby improving the thermal conductivity of the rubber by virtue of the high degree of graphitization of the carbon black.

[0058] For example, in different embodiments, the crystallinity of carbon black may be 45%, 47%, 48%, 50%, or a range consisting of any two thereof.

[0059] In a specific embodiment of the present invention, the thermal conductivity of carbon black is 0.1541 to 0.2097 W / m·K.

[0060] In a specific embodiment of the present invention, the carbon black is acetylene black.

[0061] In a specific embodiment of the present invention, the epitaxial carbon layer is grown in situ on the surface of the carbon sphere.

[0062] Another aspect of the present invention provides a method for preparing any one of the above carbon blacks, comprising the following steps:

[0063] Acetylene and methane undergo thermal cracking reaction in an environment containing carbon dioxide and isolated from air to form carbon black.

[0064] In the method for preparing carbon black of the present invention, acetylene is thermally cracked to generate a nucleation core of acetylene black, and the core grows; at the same time, the heat generated by the thermal cracking of acetylene causes the cracking of methane to form a nucleation core and generate a certain amount of hydrogen atoms, which slows down and prevents the curling and closing of carbon clusters on the surface of acetylene black to form a spherical surface of acetylene black, thereby forming an epitaxial carbon layer on the carbon ball of acetylene black. Furthermore, the carbon dioxide in the reaction system reacts with the high-temperature carbon generated by the cracking to generate a certain amount of active oxygen atoms, which have a certain etching effect on the surface of acetylene black, hindering or cutting off the carbon layer on the surface of the acetylene black carbon ball from forming a perfect spherical surface, and promoting the formation of an epitaxial carbon layer on the acetylene black carbon ball.

[0065] In a specific embodiment of the present invention, the flow ratio of acetylene, methane and carbon dioxide is 20:5:(2-7).

[0066] For example, in different embodiments, the flow ratio of acetylene, methane and carbon dioxide can be 20:5:2, 20:5:3, 20:5:4, 20:5:6, 20:5:7 or any two thereof. The corresponding carbon black structure can be obtained by setting the flow ratio of acetylene, methane and carbon dioxide in the reaction environment within the above range.

[0067] In a specific embodiment of the present invention, the gas flow directions of acetylene and methane are opposite to each other so as to facilitate uniform mixing of acetylene and methane; the gas flow direction of carbon dioxide is arranged at an angle to the gas flow directions of acetylene and methane. Further, the angle is 45° to 60°.

[0068] By adjusting the gas flow direction of carbon dioxide, acetylene and methane to meet the above conditions, the acetylene black generated by the cracking of acetylene and methane can be quickly passed through the reaction zone, avoiding the existence of the reflux zone to stop the reaction, and further promoting the formation of an epitaxial carbon layer on the acetylene black carbon ball. For example, in different embodiments, the angle can be 45°, 48°, 50°, 52°, 55°, 58°, 60° or a range consisting of any two of them.

[0069] Another aspect of the present invention provides an apparatus for implementing any one of the above-mentioned methods for preparing carbon black, such as Figure 1 As shown, it comprises: a cracking furnace body 10, wherein a reaction chamber 11 is formed inside the cracking furnace body for performing a thermal cracking reaction. The cavity structure of the reaction chamber 11 can be adapted to the structure of the cracking furnace body 10.

[0070] The cracking furnace body 10 is provided with two nozzles 13 connected to the reaction chamber 11 for introducing gas into the reaction chamber 11. The two nozzles 13 can extend into the reaction chamber 11 so as to introduce gas into the reaction chamber 11 to ensure the smooth progress of the thermal cracking reaction.

[0071] The cracking furnace body 10 is formed with a furnace head 12 arranged corresponding to the two nozzles 13 ; the furnace head 12 is provided with at least one gas introduction pipe 14 communicating with the reaction chamber 11 for introducing carbon dioxide into the reaction chamber 11 .

[0072] like Figure 2 As shown, the two nozzles 13 include a first nozzle 131 and a second nozzle 132. The first nozzle 131 is used to introduce air or methane into the reaction chamber 11, and the second nozzle 132 is used to introduce acetylene into the reaction chamber 11. The first nozzle 131 and the second nozzle 132 are arranged on opposite sides of the furnace head 12 and close to one end of the furnace head 12, and the central axis of the first nozzle 131 and the second nozzle 132 is perpendicular to the central axis of the furnace head 12. The spray directions of the first nozzle 131 and the second nozzle 132 are opposite.

[0073] In actual operation, air can be introduced through the first nozzle 131, and acetylene gas can be introduced through the second nozzle 132 to make it burn and heat up to a certain temperature (such as 850°C) to preheat the cracking furnace; then after cutting off the air supply for a period of time, methane gas is supplied from the first nozzle 131, and carbon dioxide is introduced through the gas inlet pipe 14 to cause a thermal cracking reaction, and the carbon black is collected after cooling.

[0074] In a specific embodiment of the present invention, two gas introduction pipes 14 are included. The two gas introduction pipes 14 are arranged opposite to each other on both sides of the furnace head 12 .

[0075] In actual operation, the cracking furnace body 10 may be provided with conventional heating components and temperature control components.

[0076] In a specific embodiment of the present invention, the central axis of the gas inlet pipe 14 is arranged at an angle with the central axis of the furnace head 12. Further, the angle is 30° to 45°. In subsequent specific embodiments, if no additional description is given, the angle is 40°, but it is not limited thereto.

[0077] By adjusting the angle between the central axis of the gas inlet pipe 14 and the central axis of the furnace head 12, the acetylene black generated by the cracking of acetylene and methane can quickly pass through the reaction zone, avoiding the long-term existence of the reflux zone and terminating the reaction, further promoting the formation of an epitaxial carbon layer on the acetylene black carbon balls.

[0078] In a specific embodiment of the present invention, the cracking furnace body 10 further includes a discharge port 15 , which is disposed at one end of the reaction chamber 11 away from the furnace head 12 . When the reaction is completed, the carbon black leaves the reaction chamber 11 through the discharge port 15 .

[0079] Another aspect of the present invention provides a tire bladder, comprising a rubber matrix and a filler; the filler comprises any one of the above-mentioned carbon blacks.

[0080] Among them, carbon black is used as a filler in the tire bladder, which can completely replace or partially replace the original filler in the tire bladder. Carbon black can be used as the only filler or used together with other fillers. The other fillers include but are not limited to any one or more of commercially available acetylene black, carbon black N220, carbon black N330 and carbon black N660.

[0081] In a specific embodiment of the present invention, the amount of carbon black used in the present invention is 25% to 31% of the mass of the rubber matrix.

[0082] In a specific embodiment of the present invention, the rubber matrix includes but is not limited to butyl rubber.

[0083] The tire capsule of the present invention also includes other conventional additives, including but not limited to softeners, vulcanizers, active agents and processing aids, etc. Among them, the softener includes but is not limited to castor oil, the vulcanizer includes but is not limited to vulcanized resin, the active agent includes but is not limited to chloroprene rubber and zinc oxide, and the processing aid includes but is not limited to stearic acid.

[0084] In addition, the tire bladder may also include additives such as active substances and dispersants.

[0085] Examples 1 to 3

[0086] Examples 1 to 3 provide a method for preparing carbon black having high thermal conductivity, using Figure 1 The equipment shown is prepared, comprising the following steps:

[0087] (1) Acetylene gas is heated at 10 Nm 3 / h flow rate and air at 60Nm 3 / h flow rate is introduced into the cracking furnace 10 to make it burn and heat up to 850°C to preheat the cracking furnace body 10; wherein, air is supplied through the first nozzle 131 and acetylene is supplied through the second nozzle 132.

[0088] (2) Continue to supply acetylene through the second nozzle 132, and cut off the air supply for a period of time to ensure that the cracking furnace is isolated from the air, then supply methane gas from the first nozzle 131, and supply carbon dioxide through the gas inlet pipe 14. After the thermal cracking reaction is carried out in the reaction chamber 11, the produced carbon black is collected after cooling.

[0089] In the preparation methods of Examples 1 to 3, in step (2), the flow rates of acetylene gas, methane gas and carbon dioxide are shown in Table 1.

[0090] Table 1 Flow information

[0091] serial number <![CDATA[Acetylene (Nm 3 / h)]]> <![CDATA[Methane (Nm 3 / h)]]> <![CDATA[Carbon dioxide (Nm 3 / h)]]> Example 1 20 5 2 Example 2 20 5 5 Example 3 20 5 7

[0092] Example 4

[0093] This embodiment provides a tire bladder, wherein, by weight, the amounts of the raw materials are: 100 parts of butyl rubber, 8 parts of castor oil, 30 parts of carbon black, 9 parts of vulcanized resin, 4 parts of chloroprene rubber, 6 parts of zinc oxide and 2 parts of stearic acid.

[0094] This embodiment also provides a method for preparing a tire capsule, which specifically comprises the following steps:

[0095] (1) Ingredients: Weigh each raw material separately. The amount of each raw material used is: 100 parts of butyl rubber, 8 parts of castor oil, 30 parts of carbon black, 9 parts of vulcanized resin, 4 parts of chloroprene rubber, 6 parts of zinc oxide and 2 parts of stearic acid.

[0096] (2) Mixing: butyl rubber, chloroprene rubber, stearic acid, carbon black and castor oil are sequentially put into a mixer and mixed for 4 minutes;

[0097] (3) The first coke after mixing is discharged at a temperature of 150°C, and then filtered and left to stand for 24 hours;

[0098] (4) adding the vulcanized resin and zinc oxide to the last stage of the coke for two-stage mixing for 7 minutes;

[0099] (5) The mixed second-stage coke is discharged at a temperature of 120° C. and left to stand for 24 hours;

[0100] (6) Extruding a rubber strip, extruding the second-stage rubber strip using a cold feed extruder, and controlling the temperature of the extruded rubber strip to be 130° C.;

[0101] (7) Bladder molding: The extruded rubber strip is prepared into a tire bladder using an injection vulcanizer. The vulcanization temperature is 200°C and the vulcanization mold pressure is 20Pa.

[0102] The carbon black in each tire bladder is the carbon black obtained in Examples 1 to 3, and the corresponding tire bladders are numbered as Example 4-1, Example 4-2, and Example 4-3, respectively.

[0103] Comparative Example 1

[0104] Comparative Example 1 provides a commercially available SP carbon black.

[0105] Comparative Example 1 also provides a tire bladder, which is prepared according to the method of Example 4, except that the carbon black therein is replaced with an equal weight of commercially available SP carbon black.

[0106] Comparative Example 2

[0107] Comparative Example 2 provides a carbon black, and the preparation method is the same as that of Example 1, except that: in step (2), no carbon dioxide is supplied.

[0108] Experimental Example 1

[0109] Figure 3 to Figure 5 This is a transmission electron microscope image of the carbon black obtained in Example 1 of the present invention. It can be seen from the figure that the primary particles of the carbon black of the present invention are roughly spherical, and the primary particles include carbon balls and epitaxial carbon layers located on the carbon balls. At the same time, the lattice fringes of the epitaxial carbon layer are clear and have the characteristics of graphene or graphite carbon layers, and have good thermal conductivity. Since the carbon balls of the primary particles have epitaxial carbon layers on their surfaces, point-to-surface contact can be formed between the primary particles of the carbon black, thereby improving thermal conductivity, which has obvious advantages over the point-to-point contact of traditional carbon black.

[0110] In addition, the average particle size of the primary particles of the carbon black of different embodiments and comparative examples (the average particle size of 100 primary particles observed by transmission electron microscopy) is shown in the following table. As shown in Table 2, the average particle size of the primary particles of the carbon black of the present invention is 25 to 45 nm.

[0111] Table 2 Carbon black morphology information of different embodiments and comparative examples

[0112] serial number Average primary particle size (nm) Example 1 45 Example 2 35 Example 3 25 Comparative Example 1 40 Comparative Example 2 45

[0113] Experimental Example 2

[0114] Raman spectroscopy test was carried out on the carbon black of different embodiments and comparative examples. The specific test method is: using a laser Raman spectroscopy device, several particles of the carbon black sample to be tested are placed on a glass slide, and scraped with a spatula for several times to make it flat, and the test is carried out under the following test conditions: YAG laser (excitation wavelength): 532nm, number of lines: 600gr / mm, filter: D0.6, objective lens magnification: 100 times, exposure time: 150 seconds, cumulative number of times: 2 times.

[0115] Figure 6 to Figure 8 The Raman spectra of the carbon black prepared in Examples 1 to 3 of the present invention are shown in Figure 1. The carbon black prepared in Examples 1 to 3 has a Raman spectrum of 2670 to 2690 cm -1 The full width at half maximum (Δ2D) of the 2D Raman scattering peaks appearing in the range are 125, 118, and 128 cm -1 Among them, the 2D Raman scattering peak is a symmetrical sharp single peak, and the peak position of the 2D Raman scattering peak is lower than that of general bulk graphite (about 2710cm -1 ) shifts to the left, which is the characteristic peak of the carbon layer with graphene structure different from that of bulk graphite. This also proves the existence of epitaxial carbon layer in the carbon black of the present invention, which is consistent with the result of TEM.

[0116] In addition, the 2D Raman scattering peak has a great correlation with the graphene layer structure and stacking mode. Generally, the fewer the graphene layers, the sharper and more symmetrical the 2D Raman scattering peak. The 2D Raman scattering peak of the carbon black prepared by the present invention has symmetry, and the ratio of the peak intensity of the 2D Raman scattering peak to the peak intensity of the G Raman scattering peak (I 2D / I G ) are 0.32, 0.51, and 0.61, respectively. The I 2D / I G 2, as the ratio decreases, the number of graphene layers increases, but the Raman scattering of the graphite layer on the surface of the carbon black carbon ball is removed to the contribution of the G peak of the Raman spectrum of the carbon black, and the I 2D / I G is 0.32-0.61, indicating that the carbon black has a small number of epitaxial carbon layers and has a graphene-like structure, which is consistent with the TEM results. 2D / I G When the carbon black has a carbon density of 0.32 to 0.61, the epitaxial carbon layer of the carbon black can exhibit the unique flexibility of the graphene sheet, and can improve the surface contact between the epitaxial carbon layers and between the epitaxial carbon layer and the carbon black carbon ball, so that the carbon black can have excellent thermal conductivity.

[0117] The La of the carbon blacks prepared in Examples 1 to 3 are respectively This indicates that the carbon black prepared by the present invention has a higher degree of graphitization.

[0118] At the same time, the degree of graphitization of carbon black is further characterized by crystallinity. It is measured by Raman spectroscopy that the crystallinity of the carbon black prepared in specific embodiments 1 to 3 is 47%, 50%, and 45%, respectively, which further illustrates that the carbon black prepared by the present invention can obtain a high degree of graphitization. Therefore, when it is used as a filler for rubber, a thermal conductive network can be formed in the rubber, and its high degree of graphitization can improve the thermal conductivity of the rubber.

[0119] Fig. 9 and Fig.10 They are the Raman spectra of the carbon black of Comparative Examples 1 and 2 of the present invention respectively. It can be seen from the figures that the Raman spectra of Comparative Examples 1 and 2 have no 2D Raman scattering peak.

[0120] The characteristic information of carbon black of different embodiments and comparative examples of the present invention obtained according to Raman spectroscopy is shown in Table 3.

[0121] Table 3 Characteristic information of different embodiments and comparative examples

[0122]

[0123] Experimental Example 3

[0124] The BET specific surface areas of the carbon blacks of different embodiments and comparative examples were tested according to GB / T19587-2004; the thermal conductivity of the carbon blacks of different embodiments and comparative examples was tested using a Hot Disk thermal constant analyzer; the DBP oil absorption values ​​of the carbon blacks of different embodiments and comparative examples were determined using the standard method of "GB / T3780.2-2017 Carbon Black Part 2: Determination of Oil Absorption Value", and the specific test results are shown in Table 4.

[0125] Table 4 Test results of BET specific surface area, thermal conductivity and DBP oil absorption value of different embodiments and comparative examples

[0126]

[0127] As can be seen from Table 4, the carbon black of the present invention has a high BET specific surface area, indicating that it has a developed porous structure, which increases the number of contact points between the carbon black and the rubber substrate in the rubber, and can give full play to the thermal conductivity of the carbon black. The thermal conductivity of the carbon black of the present invention is high, which is up to 79% higher than that of the commonly used commercially available carbon black. The void volume inside the carbon black aggregate is characterized by the DBP oil absorption value. The carbon black of the present invention has a high DBP oil absorption value, indicating that the chain branch structure of the carbon black of the present invention is developed and can form a good thermal conductive network.

[0128] The thermal conductivity of the tire bladders in Example 4 and Comparative Examples 1-2 was further tested using a Hot Disk thermal constant analyzer. The specific results are shown in Table 5.

[0129] Table 5 Thermal conductivity of different tire bladders

[0130]

[0131] It can be seen from the above table that the thermal conductivity of the tire bladder of the present invention is significantly improved compared with the thermal conductivity of the ordinary tire bladder, which further proves that the carbon black of the present invention has excellent thermal conductivity and can significantly improve the thermal conductivity of rubber.

[0132] In addition, compared with ordinary tire capsules, the tire capsule of the present invention only replaces traditional carbon black, which greatly saves costs compared to adding high-priced high thermal conductivity materials such as graphene and carbon nanotubes, while improving the performance and service life of the tire capsule.

[0133] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. Carbon black with high thermal conductivity, characterized in that The thermal conductivity of the carbon black is 0.1462 to 0.2097 W / m·K; The average particle size of the primary particles of the carbon black is 25 to 45 nm; the primary particles of the carbon black include a carbon sphere and an epitaxial carbon layer located on the surface of the carbon sphere; the epitaxial carbon layer is in-situ grown on the surface of the carbon sphere; In the Raman spectrum of the carbon black with an excitation wavelength of 532 nm, the ratio of the peak intensity of the 2D Raman scattering peak to the peak intensity of the G Raman scattering peak is 0.32-0.61, and the peak intensity of the carbon black at 2670-2690 cm -1 The full width at half maximum of the 2D Raman scattering peak in the range of Δ2D is 118-128 cm -1 ; The plane size of the Raman crystallite is The carbon black is acetylene black.

2. The carbon black with high thermal conductivity according to claim 1, characterized in that The carbon black meets the following characteristics: (a) BET specific surface area is 70 to 160 m 2 / g; (b) DBP oil absorption value is 240~350cm 3 / 100g.

3. The carbon black with high thermal conductivity according to claim 1, characterized in that The crystallinity of the carbon black is 45% to 50%.

4. The carbon black with high thermal conductivity according to claim 3, characterized in that The crystallinity of the carbon black is 47% to 50%.

5. The carbon black with high thermal conductivity according to claim 1, characterized in that The thermal conductivity of the carbon black is 0.1541 to 0.2097 W / m·K.

6. The method for preparing carbon black having high thermal conductivity according to any one of claims 1 to 5, characterized in that: The steps include: Acetylene and methane undergo thermal cracking reaction in an environment containing carbon dioxide and isolated from air to form carbon black.

7. The preparation method according to claim 6, characterized in that: The flow ratio of the acetylene, the methane and the carbon dioxide is 20:5:(2-7).

8. The preparation method according to claim 6, characterized in that: The gas flow directions of the acetylene and the methane are opposite; the gas flow direction of the carbon dioxide is arranged at an angle to the gas flow directions of the acetylene and the methane.

9. The preparation method according to claim 8, characterized in that: The angle is 45° to 60°.

10. A tire bladder, characterized in that: It comprises a rubber matrix and a filler; the filler comprises the carbon black described in any one of claims 1 to 5 or the carbon black prepared by the preparation method described in any one of claims 6 to 9.

Citation Information

Patent Citations

  • Thermally conductive polymer compositions containing carbon black

    CN108884267A

  • Three-dimensional graphene powder material and preparation method thereof

    CN110518251A

  • Carbon black and its production and use

    JP1995228796A

Cited By

  • High thermal conductivity carbon black, preparation method therefor, and tire bladder

    EP4806955A1